The Immune System as An Important Participant In The Development of Atherosclerosis (Review) - Don A.N; Reimnazarova G.D; Sharipova P.A; Nishanova A.A; Mirtursunov O.R (Peerian Journals Publishing, 2024)
The significant inclusiveness of the activity of the immune system in the extremely diverse mechanisms of the occurrence and development of atherosclerosis does not raise any doubts today. A modern review of literature sources on the participation of the human immune system in the pathogenesis of atherosclerosis seems relevant. Along with the latest data, information is also presented on classical fundamental theories that reveal numerous aspects of the problem under study. Conclusions include the statement that the immune system and immunopathological processes play a huge role in the pathogenesis of atherosclerosis.
Keywords: immune system; atherosclerosis; pathogenesis; theories